Enhanced Microvasculature Formation and Patterning in iPSC–Derived Kidney Organoids Cultured in Physiological Hypoxia - Schumacher, Anika; Roumans, Nadia; Rademakers, Timo; Joris, Virginie; Eischen-Loges, Maria José; van Griensven, Martijn; LaPointe, Vanessa L.S. (Frontiers in Bioengineering and Biotechnology, 2022)
Stem cell–derived kidney organoids have been shown to self-organize from induced pluripotent stem cells into most important renal structures. However, the structures remain immature in culture and contain endothelial networks with low connectivity and limited organoid invasion. Furthermore, the nephrons lose their phenotype after approximately 25 days. To become applicable for future transplantation, further maturation in vitro is essential. Since kidneys in vivo develop in hypoxia, we studied the modulation of oxygen availability in culture. We hypothesized that introducing long-term culture at physiological hypoxia, rather than the normally applied non-physiological, hyperoxic 21% O2, could initiate angiogenesis, lead to enhanced growth factor expression and improve the endothelial patterning. We therefore cultured the kidney organoids at 7% O2 instead of 21% O2 for up to 25 days and evaluated nephrogenesis, growth factor expression such as VEGF-A and vascularization. Whole mount imaging revealed a homogenous morphology of the endothelial network with enhanced sprouting and interconnectivity when the kidney organoids were cultured in hypoxia. Three-dimensional vessel quantification confirmed that the hypoxic culture led to an increased average vessel length, likely due to the observed upregulation of proangiogenic VEGF-A189 mRNA and downregulation of the antiangiogenic protein VEGF-A165b measured in hypoxia. This research indicates the importance of optimization of oxygen availability in organoid systems and the potential of hypoxic culture conditions in improving the vascularization of organoids.